Chemical stability of Ca3Co4−xO9+δ/CaMnO3−δ p–n junction for oxide-based thermoelectric generators. Issue 9 (30th January 2020) - Gunnæs, Anette Eleonora; Tofan, Raluca; Berland, Kristian; Gorantla, Sandeep; Storaas, Thomas; Desissa, Temesgen Debelo; Schrade, Matthias; Persson, Clas; Einarsrud, Mari-Ann; Wiik, Kjell; Norby, Truls; Kanas, Nikola
Abstract : The heat treatment beneficially affects the performance of an all-oxide thermoelectric generator through phase and element distribution within this p–n junction. Abstract : An all-oxide thermoelectric generator for high-temperature operation depends on a low electrical resistance of the direct p–n junction. Ca3 Co4− x O9+ δ and CaMnO3− δ exhibit p-type and n-type electronic conductivity, respectively, and the interface between these compounds is the material system investigated here. The effect of heat treatment (at 900 °C for 10 h in air) on the phase and element distribution within this p–n junction was characterized using advanced transmission electron microscopy combined with X-ray diffraction. The heat treatment resulted in counter diffusion of Ca, Mn and Co cations across the junction, and subsequent formation of a Ca3 Co1+ y Mn1− y O6 interlayer, in addition to precipitation of Co-oxide, and accompanying diffusion and redistribution of Ca across the junction. The Co/Mn ratio in Ca3 Co1+ y Mn1− y O6 varies and is close to 1 ( y = 0) at the Ca3 Co1+ y Mn1− y O6 –CaMnO3− δ boundary. The existence of a wide homogeneity range of 0 ≤ y ≤ 1 for Ca3 Co1+ y Mn1− y O6 is corroborated with density functional theory (DFT) calculations showing a small negative mixing energy in the whole range.